Management of sport organizations at the crossroad of responsibility and sustainability : perceptions, practices, and prospects around the world - Hallmann, Kirstin; Heikkinen, Suvi; Vehmas, Hanna (Sports economics, management, and policy, 2024)
This edited volume evaluates how sport organizations in the public, private, and non-profit sectors define responsible management and sustainability and what these mean in their daily operations. Using country-specific cases, the chapters provide an empirical investigation of sport organizations in each sector, analyzing managerial decisions and policies through a sustainability lens. All chapters are structured in the same way, providing a truly comparative approach. Offering insights for scholars interested in responsibility and sustainability in different context, this volume will be important to undergraduate and postgraduate sport management, event management, sport science, and sport study programs around the globe.